Data sharing among data monitoring committees and responsibilities to patients and science. - Chalmers, I; Altman, D; McHaffie, H; Owens, N; Cooke, R (2013)
Over the past three decades it has become increasingly recognized that systematic assessment of as high a proportion as possible of relevant research evidence is needed to protect the best interests of patients and the public. For example, this principle is manifested in clinical guidelines and, increasingly, in the design and monitoring of new research. For scientific and ethical reasons, those responsible for monitoring the progress of ongoing clinical trials may need to seek unpublished and interim data to protect the interests of actual or potential participants in research. The challenge facing data monitoring committees has received relatively little attention, however. In this paper we review some of the commentaries on the issue and the few accounts of actual data monitoring committee experiences. We then present details of our own recent experience as members of the data monitoring committee for the BOOST-II UK trial (ISRCTN:0084226), one of five concurrent trials assessing the level of arterial oxygen which should be targeted in the care of very premature neonates. We conclude that efficient protection both of the interests of actual or potential participants in research and of science requires that data monitoring committees have access to all relevant research, including unpublished and interim data.